Solution-Processable transparent conducting electrodes via the self assembly of silver nanowires for organic photovoltaic devices - Camic, B. Tugba; Shin, Hee Jeong; Aslan, M. Hasan; Basarir, Fevzihan; Choi, Hyosung (Academic Press Inc Elsevier Science, 2018)
Solution-processed transparent conducting electrodes (TCEs) were fabricated via the self-assembly deposition of silver nanowires (Ag NWs). Glass substrates modified with (3-aminopropyl)triethoxysilane (APTES) and (3-mercaptopropyl)trimethoxysilane (MPTES) were coated with Ag NWs for various deposition times, leading to three different Ag NWs samples (APTES-Ag NWs (PVP), MPTES-Ag NWs (PVP), and APTES-Ag NWs (COOH)). Controlling the deposition time produced Ag NWs monolayer thin films with different optical transmittance and sheet resistance. Post-annealing treatment improved their electrical conductivity. The Ag NWs films were successfully characterized using UV-Vis spectroscopy, field emission scanning electron microscopy, optical microscopy and four-point probe. Three Ag NWs films exhibited low sheet resistance of 4-19 Omega/sq and high optical transmittance of 65-81% (at 550 nm), which are comparable to those of commercial ITO electrode. We fabricated an organic photovoltaic device by using Ag NWs as the anode instead of ITO electrode, and optimized device with Ag NWs exhibited power conversion efficiency of 1.72%. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Silver nanowires; Transparent conducting electrode; Self-assembly deposition; Organic photovoltaics